Pengaruh Pemberian Bahan Amelioran terhadap Pertumbuhan dan Hasil Cabai Merah (Capsicum annum L.) di Lahan Sulfat Masam - , Koesrini; Eddy William (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2006)
High soil acidity is one of the problems causing low hot pepper yield on Acid Sulphate Soils. Using tolerant variety and application of ameliorant were some efforts to increase hot pepper yield on Acid Sulphate Soils. The objective of this research was to study the effect of ameliorant application on the growth and yield of three hot pepper varieties on Acid Sulphate Soils. This research was conducted on Acid Sulphate Soil at Barambai-Barito Kuala District-South Kalimantan on the dry season of 2004. The experiment was arranged in Split-Plot Design with three replications. The main plots were ameliorant application, i.e. control, liming 2 t.ha-1, liming 2 t.ha-1 + manure 5 t.ha-1, and the sub plots were three hot pepper varieties, i.e. Hot Chili, Jatilaba and Tit Super. The result showed that the yield of hot pepper was affected by ameliorant application, varieties and interaction between ameliorant and varieties. Liming increased yield. Hot Chili tolerated high soil acidity and had the highest yield (11.489.7 kg.ha-1) on 2 t.ha-1 liming.   Key words :  Ameliorant, hot pepper, acid sulphate soil